Effect of Magnetic Field on the Photocatalytic Degradation Dye of Nano-TiO2 - Qiu, Man-De; Xu, Li; Wang, Xiao-Yan (Asian Journal of Chemistry, 2014)
In this paper, nano-TiO2 powder, prepared by liquid deposition method, is investigated by X-ray diffraction and transmission electron microscope. Using acid red B dye as degradation simulation wastewater object, effect of different magnetic field strength under fixed magnetic field strength on nano-TiO2 photocatalytic degradation performance was studied. The photocatalytic degradation mechanism is also discussed. The results show that the magnetic field strength have great influences on the photocatalytic properties under specific light intensity, ventilation, the amount of catalyst with other factors unchanged. It is found that photocatalytic capability increases with the increase of the magnetic field. At the same time the mechanism of photocatalytic degradation is discussed based on the effects of the magnetic field and the catalyst interface charge distribution.